The real-time interaction model for transient mode investigations of a dual-piston free-piston engine generator - M. Razali, Hanipah; Mikalsen, R.; Roskilly, A.P. (Elsevier, 2022)
A free-piston engine generator is being developed worldwide as a novel means of electrical power generator for light vehicle application, which can provide a complementary solution towards reducing carbon dioxide emissions of road vehicles in general. However, the absence of a crank-slider mechanism in free-piston engines resulted in poor transient operations. Transient real-time modelling and simulation can provide the interaction between in-cylinder combustion with dynamics of piston motion, which has not been fully explored previously. This paper presents a real-time interaction model between dynamics of the piston motion and thermodynamics of the in-cylinder combustion of a two-stroke spark ignition dual-piston free-piston engine generator for transient operation investigations. The simulation model was developed based on the working prototype and comprised of zero- and one-dimensional sub-models interacted in real-time governed by a single timestep. The study focuses on three critical transient modes: motoring, starting and generating for the transient performance investigation. A series of experimental results during motoring was used for validating the simulation model, which showed good agreement between simulation and experiment results with 2–5% errors. The targeted brake thermal efficiency is around 20–30% at 50–60 Hz engine speed which has been shown achievable. Transient speeds of 10 and 25 Hz produced higher combustion pressure around the top dead centre but suffered pumping loss at the end of the expansion stroke. The lower peak pressures at 50 and 60 Hz have contributed to the lower brake mean effective pressure values. Maximum brake thermal efficiency of 25.8% lies in the mid-range of compression ratios between 10:1 to 15:1 while at the cyclic speeds of 50 Hz to 60 Hz. Maximum brake mean effective pressure contour occurs between 5 and 12.5 compression ratios and corresponding speeds of 10 to 30 Hz. It was observed that the excess energy from combustion results in piston overshoot condition while insufficient energy prevents the piston from achieving the targeted stroke and compression ratio. Knock events were observed for high compression ratio cases regardless of engine speed. Predictive stroke control and knock detection capability are the main contribution of the real-time interaction model presented in this paper for realistic transient operation investigation and performance prediction of the dual-piston free-piston engine generator.